Little House : Laura and Mr. Edwards - Henson, Heather; Wilder, Laura Ingalls, 1867-1957.; Wilder, Laura Ingalls, 1867-1957.; Wilder, Laura Ingalls, 1867-1957.; Graef, RenGee (New York : HarperCollinsPublishers, 1999)
When Laura and her family move from Wisconsin to Kansas, they make friends with a helpful neighbor who comes to their aid later when they settle in the Dakota Territory.
"Text adapted from Little house on the prairie; By the shores of Silver Lake; and The long winter"--T.p. verso.
Keywords: Wilder, Laura Ingalls, -- 1867-1957 -- Fiction; Wilder, Laura Ingalls, -- 1867-1957 -- Fiction; Frontier and pioneer life -- Fiction; Neighbors -- Fiction; Chapter book